Anti-Memoirs - Malraux, A. (New York First American Edition, 1968)
In Anti-Memoirs, the human condition is seen in concentration camps, in the midst of political upheavals, in the power and imagination of great leaders, and in the testing of mans courage and endurance. by relating his actions and disclosing his thoughts, Malraux demonstrates the purpose and special meaning of his life and of all human life.
Keywords: Fiction